Assessment and indicators of kinematic behavior and perceived fatigability - Silva-Migueis, Helena; Martínez-Jiménez, Eva María; Casado-Hernández, Israel; Dias, Adriano [UNESP]; Monteiro, Ana Júlia; Martins, Rodrigo Brandão; Bernardes, João Marcos [UNESP]; López-López, Daniel; Gómez-Salgado, Juan (FapUNIFESP (SciELO), 2024)
OBJECTIVE: The objective of this study was to investigate the relationship between upper limb kinetics and perceived fatigability in elderly individuals during an upper limb position sustained isometric task. METHODS: A total of 31 elderly participants, 16 men (72.94±4.49 years) and 15 women (72.27±6.05 years), performed a upper limb position sustained isometric task. Upper-limb acceleration was measured using an inertial measurement unit. Perceived fatigability was measured using the Borg CR10 scale. RESULTS: Higher mean acceleration in the x-axis throughout the activity was associated with higher final perceived fatigability scores. Moderate correlations were observed between perceived fatigability variation and mean acceleration cutoffs in all axes during the second half of the activity. In women, significant correlations were found between all perceived fatigability cutoffs and mean acceleration in the y- and x-axes. However, in men, the relationships between perceived fatigability variation and mean acceleration were more extensive and stronger. CONCLUSION: The acceleration pattern of the upper limb is linked to perceived fatigability scores and variation, with differences between sexes. Monitoring upper limb acceleration using a single inertial measurement unit can be a useful and straightforward method for identifying individuals who may be at risk of experiencing high perceived fatigability or task failure.
Keywords: Accelerometry; Aged; Exercise therapy; Fatigue; Symptom assessment; Upper extremity